Development and validation of headspace gas chromatography with a flame ionization detector method for the determination of ethanol in the vitreous humor - Mihajlović Filip; Andrić Ivana; Slović Živana; Vujović Maja; Piskulić Kristina; Đorđević Snežana (Open Medicine)
Qualitative and quantitative testing of ethanol in post-mortem samples is an important analytical procedure that provides accurate, precise, and reliable results. Given the complexity of the issue, obtaining a realistic picture of lifelong alcoholemia requires supporting blood ethanol findings with analyses of alternative samples, primarily vitreous humor (VH).